Specific Investment Under Negotiated Transfer Pricing: An Efficiency Result. - Edlin, Aaron S.; Reichelstein, Stefan (The Accounting Review, 1995)
Analyzes a system of negotiated transfer pricing in which divisions can agree on a simple fixed-price contract and renegotiate this contract on arrival of better information. Provision of effective protection for their specific investments.